2014
DOI: 10.1002/elps.201400017
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in enrichment and separation strategies for mass spectrometry‐based phosphoproteomics

Abstract: Due to the significance of protein phosphorylation in various biological processes and signaling events, new analytical techniques for enhanced phosphoproteomics have been rapidly introduced in recent years. The combinatorial use of the phospho-specific enrichment techniques and prefractionation methods prior to MS analysis enables comprehensive profiling of the phosphoproteome and facilitates deciphering the critical roles that phosphorylation plays in signaling pathways in various biological systems. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 116 publications
0
28
0
Order By: Relevance
“…Using certain phosphorylation enrichment methods (see below) and optimization of MS/MS instrumentation, many MS-based studies have successfully identified thousands of phosphorylated proteins. 66 For very dynamic modifications such as phosphorylation, SUMOylation, and acetylation, inhibitors targeting eraser enzymes are routinely added into sample collection protocols to reduce PTM loss during sample preparation. 67 …”
Section: Mass Spectrometry and Its Applications To Identify Histonmentioning
confidence: 99%
“…Using certain phosphorylation enrichment methods (see below) and optimization of MS/MS instrumentation, many MS-based studies have successfully identified thousands of phosphorylated proteins. 66 For very dynamic modifications such as phosphorylation, SUMOylation, and acetylation, inhibitors targeting eraser enzymes are routinely added into sample collection protocols to reduce PTM loss during sample preparation. 67 …”
Section: Mass Spectrometry and Its Applications To Identify Histonmentioning
confidence: 99%
“…However, the specific profiling of these protein species is normally obstructed due to low stoichiometry, wide dynamic range, and various isoforms of them in the biological systems, posing significant challenges to current analytical techniques . Fortunately, these challenges can be alleviated to some extent by enriching phosphoproteins/peptides and glycoproteins/glycopeptides prior to MS analysis . HPLC‐based technique has been developed for enrichment and fractionation of phosphoproteins and glycoproteins, and various chromatographic materials have emerged to meet these requirements.…”
Section: Application Of Monolithic Materials For Enrichment and Fractmentioning
confidence: 99%
“…In recent years, phosphoproteomics using mass spectrometry has dramatically improved in sensitivity, accuracy and methodology and has become a major technology for identifying and quantifying protein phosphorylation [3][4][5]. Many phosphorylation sites in various species and various cells have been identified by mass spectrometry-based phosphoproteomic research [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%